A new systems engineering structured assurance methodology for complex systems - Farnell, G. P.; Saddington, Alistair J.; Lacey, Laura J. (Elsevier, 2018)
As technology advances, systems behaviour becomes more difficult to predict and control, resulting in a lack of systems assurance across the supply chain. Here we describe a structured approach to address the assurance of complex systems developed and operated within highly regulated environments. The new approach is based on a methodology that can address both new and legacy systems, and influences system intervention. We propose an enterprise approach by observing the importance of all organisational contributions to a safe working system throughout the intended project life cycle. This research was catalysed by the need to address the certification of the F-35B stealth fighter for UK operations from 2012 onwards. We offer a pragmatic strategy to achieve systems control by adopting a holistic approach to systems engineering while promoting the development of an enabling environment that can determine system threats and enable appropriate controls. We propose a systematic coordination process to minimise the potential for ‘organisational drift’. This holistic approach to systems engineering and assurance is defined as ‘systems engineering structured assurance’. The methodology provides a confidence assessment for a particular product or system while remaining agnostic to regulatory constraints. The diligent completion of the methodology increases systems confidence and informs the regulatory environment.
Keywords: Structured assurance; Systems; Engineering; Safety; Methodology; Complex